(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article deals with the improvement of the system managing the forest sector business processes based on some flexibility. Some flexibility significance of business processes carrying out by entities in the current economic environment has been confirmed. The flexibility of the business processes in the forest sector has been proved as a core driver of its effective functioning. Moreover, it ensures the production mobility with changes of customer needs. The own interpretation of the concept of "flexibility" has been given, as well as the flexibility assessment technique of business processes has been improved and tried out in business processes of the forest sector. The control system has been studied as it is based on the implementation of industrial strategies taking into account the flexibility of any production activities.